DESIGNING AN ENGLISH VOCABULARY WORKBOOK FOR HOSPITALITY STUDENTS BASED ON CORPUS-BASED APPROACH - Andi Rizki Fauzi; Suradi Suradi (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
The research about the use of corpus-based approach in teaching English for Specific Purposes (ESP) to improve the students' vocabulary mastery has been conducted by many researchers. However, the product of the materials in teaching and learning vocabulary which laverages the use of corpus is very limited. For that reason, this study is aimed to design a prototype of English vocabulary workbook for Hospitality students based on corpus-based approach in determining the content, task, and activities carried out. This research uses Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model as the procedure to create a valid, practical, and effective English vocabulary workbook for Hospitality students and corpus-based approach will be used in determining the target words, task, and activities in the workbook. Based on the result of analysis using Wilcoxon test, it can be seen that the Asymp.Sig (2-tailed) is 0.000. As the value of 0.000 is smaller than 0.05, it can be concluded that there is a significant difference between the results of student learning before and after using the workbook developed.